Evaluation of Participation Level of Adolescents with Cerebral Palsy - Uzma Javed, Maleeha Fuad, Sajid Mahmood, Bushra Rani, Waqas Latif, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Adolescence is a time of rapid development in many facets of an individual’s physiological, cognitive, and interpersonal traits, but it also comes with some complexities. Aim: To evaluate the level of participation in different domains of life situations in adolescents with Cerebral Palsy. Study design: Cross-sectional study. Methodology: Study conducted in adolescents with Cerebral Palsy between age 10 – 19, with motor impairment level I, II and level III on GMFCS. Sample size was 84 participants. Questionnaire of Young People’s Participation (QYPP) was used to evaluate participation in different activities and domains of life. Statistical analysis: Analysis of data was done by SPSS v.26. Results: The highest percentage score was observed for Autonomy followed by Getting on with other people, Home life, Reception and Leisure and School or College life. The least percentage score was seen for two domains i.e., Work life and Preparing for the future. It was observed that participants in higher age category had higher score except school or college life domain but no significant difference was evident as per p-value. Conclusion: It was concluded that overall frequency of participation levels proved inadequate in adolescents with CP in all the domains tested. Keywords: Adolescents, Cerebral Palsy, Personal Autonomy and Social Participation.